Recessive Arrhythmogenic Right Ventricular Dysplasia Due to Novel Cryptic Splice Mutation in PKP2 - Awad, Mark M. (2006)
Arrhythmogenic right ventricular dysplasia (ARVD) is a genetic disorder resulting in fibrofatty replacement of right ventricular myocytes and consequent ventricular arrhythmias. Heterozygous mutations in PKP2 encoding plakophilin-2 have previously been reported to cause dominant ARVD with reduced penetrance. We report the first case of recessive ARVD caused by mutations in PKP2. Candidate gene analysis in a typical proband with this disorder identified a novel homozygous mutation in PKP2 (c.[2484C>T]+[2484C>T]), which is predicted to be translationally silent (p.Gly828). Analysis of the proband’s mRNA, however, shows that this mutation causes predominantly cryptic splicing, with a 7-nucleotide deletion in exon 12. The ensuing frame shift disrupts the last 54 amino acids of plakophilin-2 and extends the open reading frame by 145 nucleotides (48 amino acids) into the 3’ untranslated region. Haplotype analysis demonstrates the absence of remote consanguinity. Heterozygous family members produce approximately 60% of properly spliced PKP2 and do not have manifestations of ARVD. Further analysis of PKP2 mRNA sequence revealed two additional alternatively spliced transcripts. The possibility of cryptic or alternative splicing should be considered with identification of apparently synonymous nucleotide substitutions in this gene.